Development of distance measurement accuracy technology in physical activity tracking applications with a reward point system - Setiono, Oki; Nurjanah, Nurjanah; Mubarokah, Kismi; Haikal, Haikal; Iqbal, Muhammad (Institute of Computer Science (IOCS), 2025)
In the digital era, physical activity tracking applications have become increasingly popular as tools to monitor body health and encourage healthy habits. However, the accuracy of distance measurements used by many of these applications still faces challenges, especially in environments with GPS signal interference. This research aims to develop a system that integrates GPS technology and accelerometer sensors to improve the accuracy of distance measurements in physical activity tracking applications. The developed system was tested through a prototype to evaluate the effectiveness of combining these two technologies in improving measurement results. Additionally, this research also designs a database system for efficient physical activity data management, enabling real-time monitoring. To enhance user motivation, a reward point system was applied as a gamification element to encourage further engagement in physical activities. The results of this research show that the combined use of GPS and accelerometers was able to improve measurement accuracy, with errors ranging from 2.4% to 4.2%, depending on the type of activity performed. Walking activities demonstrated higher accuracy compared to running. The reward point system was also proven to be effective in motivating users to be more active. This research provides an important contribution to the development of more accurate, efficient health applications that can improve both physical and mental well-being